STUDENTS' PERSPECTIVES ON ONLINE LEARNING - ARE THEIR EXPECTATIONS MET BY CURRENT TEACHING PRACTICES? - Iulia GONŢA; Cristina TRIPON (National Centre for Policy and Evaluation in Education, 2021)
The challenges of online learning, created by the COVID-19 pandemic, have prompted a significant demand in researching this particular field of education. The adaptation to online learning, unfortunately, was applied in a context of unprepared teachers and students. This situation was caused by the new format of education, which differs significantly from massive open online courses, traditional learning or distance learning. The new hybrid model of education, prompted by the pandemic, has certainly become a trend that could incite future transformations in terms of teaching and learning. To better understand the specifics of this type of online learning, we asked the students (N = 705) from the University POLITEHNICA of Bucharest to express their opinion on their learning experience during the pandemic. The survey included the problems and expectations of the interviewees, and the research results were analyzed in the article. Our goal was to improve educational practices in the virtual educational environment. In this regard, we analyzed the important components of online learning, focusing on the following ones: the quality of the educational resources used to support the content, the improvement of the quality of the teacher- student relationships, time management, online assessment. The article also provides solutions for effective online learning, from the students' perspective.